EFFECT OF WORK ENVIRONMENT AND MOTIVATION ON WORKLOAD AND ITS IMPLICATIONS ON EMPLOYEE PERFORMANCE PT. PLN (PERSERO) UP3 KEBON JERUK - Parulian, Sahat; Ahmad Hidayat Sutawijaya (Dinasti International Journal of Digital Business Management, 2020)
This study aims to determine and clarify the effect of work environment and work motivation for workload and its implementation on employee performance. Respondents 67 employees (entire population). Data collection is done through interviews and questionnaires. Data were analyzed using path analysis (SmartPls 3.0 software) and correlation matrix between dimensions (SmartPls 3.0 software). The results showed that: (1) Work Environment and Motivation both partially and simultaneously affect Employee Performance; (2) Work environment, motivation and workload both partially and simultaneously affect employee performance; (3) Workload mediates the work environment and motivation on performance. Based on the analysis of the correlation matrix between dimensions, to improve the Work Environment, which has a positive correlation with Workload, it is recommended to maintain and improve the dimensions of Non-Physical Work Environment and also for employee performance also to improve the Physical Environment dimension. To increase motivation, which has a positive correlation with workload, it is recommended to maintain and improve hygiene. And for employee performance that is increasing the dimensions of intrinsic appreciation. To increase the workload that has a positive correlation with employee performance it is advisable to maintain and improve the dimensions of frustration